Pesimism, optimism și încredere în instituții în România actuală - Alexandra Deliu (Sociologie Românească, 2024)
This article uses data from the Eurobarometer series to comparatively present Romania's evolution of optimism/pessimism and trust in institutions, compared to the EU from 2017 to 2023. The premise of the discussion is that the overlap of multiple crises – the health crisis associated with the COVID-19 pandemic, the geopolitical crisis stemming from the war in Ukraine, and the economic crisis resulting from both – leads to changes regarding individuals' outlook on both their own future (optimism/pessimism) and the social environment around them (trust in institutions). The data presented here suggest that Romania stands out from the EU due to a high degree of instability in perceptions, as well as the observation that politics and daily life seem to be two disconnected domains in Romania.